CONCEPTUAL CONSIDERATION OF THE REASONS FOR THE DEPLOYMENT AND COLLAPSE OF THE PROTESTS IN BELARUS IN 2020 - Tukalenko (Тукаленко Інна Анатоліївна), Inna (Politology bulletin, 2021)
The study of the reasons for the deployment and collapse of protests in Belarus was conducted on the basis of fundamental approaches to studying the nature of protest movements: political opportunity structure, resource mobilization and interactive approach. The reasons for the outbreak of the protest wave in Belarus were analyzed in three areas: global, national and eventual (situational). Both global trends and intra-system factors were taken into account, including the impact of evolutionary modernization and development of network technologies on the shaping of the demand for democracy, changes in social and class structure of Belarusian society, the ferment of dissatisfaction with current political regime and situational reactions to protests. The reasons for the defeat of the protests were clarified and the dominance of two of them — the use of disproportionately harsh government response to non-violent forms of protest activity of citizens and the inability of protesters to cause a serious split in the ruling class — was substantiated.

Дослідження причин розгортання та поразки протестів у Білорусі було здійснено на основі базових підходів до вивчення протестних рухів: інтерактивного, структури політичних можливостей та ресурсної мобілізації. Причини сплеску протестної хвилі в Білорусі аналізувалися у трьох площинах: глобальній, національній та подієвій (ситуативній). Враховувалися як загальносвітові тенденції і чинники так і внутрішньосистемні, як от: вплив еволюційної модернізації та розвитку мережевих технологій на формування запиту на демократію, зміни в соціально-класовій структурі білоруського суспільства, ферментація настроїв незадоволення існуючим політичним режимом та ситуативні реакції влади на активізацію протестних дій. З’ясовано причини поразки протестів та обґрунтовано домінуюче значення двох з них: застосування непропорційно жорстокої відповіді влади на ненасильницькі форми протетсної активності громадян і неспроможність учасників протесту внести серйозний розкол у правлячий клас.
КОНЦЕПТУАЛЬНЕ ОСМИСЛЕННЯ ПРИЧИН РОЗГОРТАННЯ ТА ПОРАЗКИ БІЛОРУСЬКИХ ПРОТЕСТІВ 2020 РОКУ
Keywords: protests in Belarus; wave of protest; nonviolent protest; reasons for protest; democratization; протести в Білорусі; протестна хвиля; ненасильницький протест; причини протесту; демократизація